On the Logarithmic Regularity Conditions for the Variable Exponent Hardy Type Inequality. (22nd April 2014) - Harman, Aziz; Keleş, Mustafa Özgür
Abstract : We discuss a logarithmic regularity condition in a neighborhood of the origin and infinity on the exponent functionsq x ≥ p x andβ x for the variable exponent Hardy inequalityx β · - 1 ∫ 0 x f t d t L p · 0, l ≤ C x β · f L p · 0, l to hold.